3D data obtained with a MicroScribe digitising arm and photogrammetry to address bioarchaeological research questions - Plomp, Kimberly; Collard, Mark; Dobney, Keith (Dryad, 2022)
Virtual methods for studying human remains are becoming increasingly
popular in bioarchaeology, and the rate of technological innovation in the
last few years has been such that we now have multiple options to choose
from when collecting data. This raises the question of whether datasets
generated with different methods are transposable. In the study reported
here, we investigated whether it is valid to combine 3D data obtained with
a MicroScribe digitising arm and 3D data collected via photogrammetry. We
did so by simulating a population-based analysis similar to those commonly
undertaken in bioarchaeology. Our sample comprised 19 crania from two
ethnic groups, Ancient Egyptians and Guanches, and the landmarks we
employed pertained to facial shape. The analyses yielded several findings.
First, we found that photogrammetry was significantly more precise than
the MicroScribe digitising arm. Second, the photogrammetry-based method
revealed the existence of facial shape differences between the two ethnic
groups that were not captured by the MicroScribe-based method. Third, we
found that the two methods did not consistently capture the same facial
shapes—they did for one of the ethnic groups but not for the other.
Fourth, the analyses indicated that using the two methods can result in
ethnic group-level differences in facial shape when they are applied to
individuals from a single ethnic group. Lastly, the two methods of data
collection yielded different patterns of variation in facial shape.
Together, these findings suggest that combining 3D landmark coordinates
collected with a MicroScribe and those obtained via photogrammetry may
introduce considerable error into an analysis, and, consequently,
bioarchaeologists should be cautious about doing so.
The sample comprised 19 crania from two different ethnic groups:
Pre-Spanish Guanches from the Canary Islands (n=11) and Ancient Egyptians
(n=8). Collected in the 19th century, the crania are currently curated at
the University of Edinburgh’s Anatomical Museum. Individuals were recorded
as female or male based on the original collection records (i.e. we did
not sex them ourselves). Eight of the individuals were female and 12 were
male. Only adult crania were included in the sample in order to avoid the
confounding effects of ontogeny; individuals were judged to be adult on
the basis of dental eruption. Further information about the sample can be
found in the Supplementary Information. The specific photogrammetry method
we used was outlined by Evin et al. (2016). We took 150 photographs of
each cranium with an eight megapixel digital single-lens reflex Canon EOS
77D camera and a 50mm lens. With the cranium placed on a rotating table,
the photographs were shot at intervals of approximately 10°. Following
Evin et al. (2016), a 3D scale was employed as a target marker. We then
used Agisoft Metashape (Agisoft, 2019) to create a 3D model of the cranium
from the photographs. We aligned all the photographs with the accuracy
level set to ‘high’, and then produced a depth map, again with the
accuracy level set to ‘high’. Next, we used the depth map to create a
mesh. Thereafter, we exported the mesh as a 3D model (.ply). Lastly, the
3D model was imported into MorphoDig (Lebrun 2018) and the 3D Cartesian
coordinates of 13 facial landmarks captured twice (Figure 1). All
landmarks were Type I landmarks, according to Bookstein’s (1997) widely
used scheme. We selected Type I landmarks because they are the most
reliable type of landmark (Bookstein, 1997) and thus should maximise the
probability of the two methods yielding data that are statistically
indistinguishable. The digitising arm we used was a MicroScribe MLX
(https://gomeasure3d.com/microscribe/) with a standard stylus tip. The
landmarks we recorded were the same as the ones we captured on the
photogrammetry-derived models (Figure 1). A single observer (KAP) operated
the MicroScribe to avoid the problem of inter-observer error. KAP has
considerable experience collecting data with a MicroScribe (e.g. Plomp et
al. 2013, 2015, 2019ab, 2020, 2021ab). As with the photogrammetry, the
coordinates of the landmarks were collected twice. We employed the dataset
in five analyses. In the first, we investigated whether the landmarks
recorded with the two methods of data collection had the same level of
precision. To accomplish this, the entire dataset was subjected to
generalised Procrustes analysis (GPA), which converts the Cartesian
coordinates for a given landmark configuration into Procrustes coordinates
by removing translational and rotational effects and scaling the landmark
configuration to centroid size (Slice 2007). The Procrustes coordinates
are provided in this dataset.
Keywords: FOS: Social sciences; Geometric Morphometrics; Virtual anthropology; photogrammetry; digitising arm; Microscribe; facial shape; Crania; 3D shape analysis